2021
DOI: 10.17305/bjbms.2021.5703
|View full text |Cite
|
Sign up to set email alerts
|

Audiological and vestibular evaluations in vitiligo patients

Abstract: The aim of this paper was to investigate audiological abnormalities and potential vestibular injury in a sample of vitiligo subjects. Thirty-five patients with non-segmental vitiligo (NSV) were enrolled in the study. They underwent pure tonal audiometry (PTA), vestibular Fitzgerald-Hallpike caloric test, C-VEM, and O-VEMP testing.  The χ2 test and multiple regression analysis were performed. At PTA, 69% of patients presented with bilateral hearing loss, 8% monaural hearing loss, and 23% normal values. Bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Similarly, Abd El Mageed et al [26] reported that 27 (42.9%) patients had delayed latency. In contrast, Manno et al [28] cVEMPs findings revealed abnormal latency of P13 in 5 patients: One of them with a unilateral absent response. Latency of n23 was affected in only 2 patients, 1 with an absent response.…”
Section:  Cvempmentioning
confidence: 82%
See 2 more Smart Citations
“…Similarly, Abd El Mageed et al [26] reported that 27 (42.9%) patients had delayed latency. In contrast, Manno et al [28] cVEMPs findings revealed abnormal latency of P13 in 5 patients: One of them with a unilateral absent response. Latency of n23 was affected in only 2 patients, 1 with an absent response.…”
Section:  Cvempmentioning
confidence: 82%
“…While 4 patients (6.3%) showed unilateral absent waves. Manno et al [28] found that 1/35 (3%) had no cVEMPs response. In comparison, Koura et al [27] found that cVEMP was absent bilaterally in 8 of 30 (26.6%) and absent unilaterally in 6 of 30 (20%) in the left ear.…”
Section:  Cvempmentioning
confidence: 98%
See 1 more Smart Citation
“…Scientists suspect that hearing degeneration may be related to NSV. In addition, they recommend performing bithermal caloric testing, C-VEMP and O-VEMP, even in asymptomatic individuals, to assess vestibular damage [19].…”
Section: Manno Et Al Investigated Audiological Abnormalities and Pote...mentioning
confidence: 99%